Pengaruh Kinerja Lingkungan, Biaya Lingkungan Terhadap Kinerja Keuangan dan CSR Sebagai Variabel Mediasi - Christiani, Aqnisa; Rahmadhani, Sari (Forum Kerjasama Pendidikan Tinggi, 2024)
This study is to determine whether CSR functions as a mediating variable in the relationship between environmental performance/environmental costs and financial performance in energy sector companies listed on the Indonesia Stock Exchange in 2021-2023. This means assessing whether the impact of environmental performance or environmental costs on a company's financial performance is mediated by the company's CSR efforts. The method used is purposive sampling. Environmental performance has no effect on financial performance because the p-value shows a value of 0.189 greater than 0.050 so the hypothesis is rejected. Environmental costs have a significant negative effect on financial performance, the p-value shows that the value of 0.000 is smaller than 0.05. , CSR has a significant negative effect on financial performance, with a p-value showing a value of 0.024 smaller than 0.05. Environmental Performance has a significant negative effect on CSR, with a p-value showing a value of 0.024 less than 0,050.